2021
DOI: 10.1038/s41396-021-01152-0
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian gut metabolomes mirror microbiome composition and host phylogeny

Abstract: In the past decade, studies on the mammalian gut microbiome have revealed that different animal species have distinct gut microbial compositions. The functional ramifications of this variation in microbial composition remain unclear: do these taxonomic differences indicate microbial adaptations to host-specific functionality, or are these diverse microbial communities essentially functionally redundant, as has been indicated by previous metagenomics studies? Here, we examine the metabolic content of mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 106 publications
0
21
0
Order By: Relevance
“…One of the most compelling potential applications of EQO is the identification of functional groups responsible for the production or consumption of metabolites in gut microbiome data. We leveraged an animal gut microbiome dataset with 101 fecal samples from a wide range of 25 mammalian species, accompanied by 74 peak features that are detected by GC-MS in >80% samples 20 . Unlike the case of nitrate discussed above, which has been a major focus of research in since the early days of environmental microbiology, the metabolic processes that drive the production or consumption of metabolites in animal guts are much less understood.…”
Section: Mapping Metabolites To Functional Groups In Animal Microbiomesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most compelling potential applications of EQO is the identification of functional groups responsible for the production or consumption of metabolites in gut microbiome data. We leveraged an animal gut microbiome dataset with 101 fecal samples from a wide range of 25 mammalian species, accompanied by 74 peak features that are detected by GC-MS in >80% samples 20 . Unlike the case of nitrate discussed above, which has been a major focus of research in since the early days of environmental microbiology, the metabolic processes that drive the production or consumption of metabolites in animal guts are much less understood.…”
Section: Mapping Metabolites To Functional Groups In Animal Microbiomesmentioning
confidence: 99%
“…If the environment is constant across samples, the approach we present in this paper can identify groups of taxa that are most stably maintained across replicates, likely representing ‘species portfolios’ with redundant function. Below we provide a detailed explanation of the approach and show how it can successfully be applied across various data sets, ranging from replicate microcosms 4 to the TARA Oceans microbiome 19 to metabolomic profiles of animal gut microbiomes 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome can provide energy, in the form of short-chain fatty acids, to its host and maintain the gut homeostatic balance ( Gonçalves et al, 2018 ; Markowiak-Kopeć and Śliżewska, 2020 ). Many factors affect gut microbiome composition and function, including diet ( Huang et al, 2022 ), phylogeny ( Wang et al, 2019 ; Gregor et al, 2022 ), and environment ( Gacesa et al, 2022 ; Wang et al, 2022 ). When a factor surpasses the other influencing factors, the gut microbiome converges to adapt toward this dominant factor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to animals with specialized diets, species with closer phylogenetic relationships or similar behavior have similar gut microbiome compositions ( Gregor et al, 2022 ). Amato et al (2019) found that host phylogeny outweighs the dietary niche in structuring primate gut microbiomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent papers have proposed to use the metabolomic approach for the classification of species. This approach has primarily been applied to plant species and subspecies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ] (the approach has been known in phytochemistry since the 1960s as ‘chemotaxonomy’) and to a lesser extent to fungi species [ 16 , 17 ], animal microbiomes [ 18 ] and human microbiomes [ 19 ]. Among these papers, some authors used an integrative approach—a combination of metabolomics with genome sequence analyses [ 10 , 11 , 12 , 16 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%